Exploration Of Sosrokartono's Moral Teachings And Their Resonance With The Axiology Of Islamic Education - Witoyo, Nurryanto Midi; Abdi, Supriyanto (Universitas Islam Indonesia, 2024)
This study aims to explore and examine the moral teachings of Raden Mas Panji Sosrokartono, an important figure in Javanese moral and spiritual tradition, and their resonance with the axiology of Islamic education. More specifically, the study examines Sosrokartono's moral teachings as reflected in his symbolic names (sinandi) such as